First Molecular Identification of Sunfish in North Bali Water - Riawan, I Made Oka; Setiabudi, Gede Iwan; Merdana, I Made; Mariasa, I Putu Mangku; Wirasastra, Kadek Teguh (Advances in Tropical Biodiversity and Environmental Sciences, 2019)
Stranded Sunfish in North Bali with full body we collect to do molecular identification. Samples were amplified at the d-loop locus (control region) using the PCR (Polymerase Chain Reaction) method. Primers used in PCR are H16498 as primary front (forward) and L15812 as reverse primer. Similarity value of 95% after alignment with Mola ramsayi (accession number accession AY940824) on GenBank, and the gaps of the nucleotide just 1%. The stranded sunfish identified using partial sequence mtDNA is the same species as the species Mola ramsayi.